Sosialisasi Strategi Pemasaran Produk Melalui Media Sosial Di Toko Arjuna Collection - Aprilia, Izra Putri; Soleh, Ahmad; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2024)
Arjuna Collection Shop is a shop that operates in the field of school uniform sales services. Employees' knowledge of marketing strategies is very important to increase product sales. Optimizing social media and attractive product branding can expand promotions and attract the attention of schools in Bengkulu City to buy products. This is one of the important points for advancing especially those in the Arjuna Collection Store. Therefore, socialization regarding marketing strategies related to utilization is needed social media as a marketing medium. The products produced by some at the Arjuna Collection Shop still seem unknown to schools in Bengkulu City. The introduction of social media as a marketing strategy is very important considering that technological developments are now starting to advance. Most people now carry out buying and selling transactions via the internet or social media because it is more effective and efficient. For this reason, service activities were carried out for female employees which included providing insight into the socialization of marketing strategies for products via social media at the Arjuna Collection Store for products that could be promoted via social media.